Strategi Pembelajaran Analogi dan Kemampuan Pemahaman Konsep Matematika - Ketut Rendrayana; I Made Suarsana; Ni Nyoman Parwati (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2020)
This study aimed to determine the effect of analogy learning strategies on the ability to mathematical conceptual understanding. This research is a quasi-experimental study using pretest-posttest control group design. The research population was class VIII of SMP Negeri 2 Sawan in the academic year 2019/2020, which was then sampled using cluster random sampling techniques to obtain students in class VIIIA and VIIIC as an experimental group and students in class VIIIB and VIIID as a control group. The ability to understand students' mathematical concepts was tested using essays tests both pre-test and post-test. After the data is collected, it is then analyzed using the one-way ANACOVA test with a significance level of 5%. Based on the results of research conducted, obtained FA * = 17,369 ≥ F table = 3,918. These results indicate that the student sability to understand mathematical concepts who are taught by using analogy learning strategies are better than conventional learning. Therefore analogy learning strategies have a positive influence on the ability to understand mathematical concepts.